Analyzing Bandwidth on the Microwave Absorber by the Interface Reflection Model - 乔亮 王涛 梅忠磊 李喜玲 隋文波 唐丽云 李发伸 (Chinese physics letters, 2016)
Metallic flaky sendust particles are prepared for use as fillers in electromagnetic attenuation composites. We report the interface reflection model to divide the broad bandwidth into electromagnetic loss and quarter-wavelength （λ/4） cancelation. Combining with the face reflection calculation, we identify the electromagnetic loss originated from skin effect, which is used to explain over half of the absorbed energy in high frequency band. Most impor- tantly, the unique electromagnetic loss cannot generate the reflection loss （RL） peak. Using the phase relation of face reflection, we show evidence that the λ/4 cancelation is vital to generate the RL peak. The calculated energy loss agrees well with the experimental data and lays the foundation for further research.